SPECIFIC FEATURES OF RADIO JOURNALISM (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the place and role of radio in the media. It also focuses on the specifics of radio journalism in the media and is aimed at consolidating and supplementing theoretical knowledge, practical skills and information provided in this area. The artistic means of radio journalism are widely discussed and analyzed in detail. Various aspects related to the professional activities of a radio journalist are considered. The role of radio in the formation of public consciousness and the role of radio in modern society will be discussed. That and a number of other issues will be discussed.
Keywords: radio journalism, mass media, radio, TV, newspaper, radio journalist, function, factor, activity, creativity, audience, feature.